Equations balanced on the previous day |
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + H2O(l) =>
2 HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + H2O(l) =>
2 HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
HI2 + K = KI + H2 =>
2 HI2 + 4 K = 4 KI + H2
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
HC2H3O2(aq) + Ca(OH)2(aq) = H2O(l) + Ca(C2H3O2)2(aq) =>
2 HC2H3O2(aq) + Ca(OH)2(aq) = 2 H2O(l) + Ca(C2H3O2)2(aq)
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
ClCH2COOH + NH3 = H2NCH2COOH + NH4Cl =>
ClCH2COOH + 2 NH3 = H2NCH2COOH + NH4Cl
HC2H3O2(aq) + Ca(OH)2(aq) = H2O(l) + Ca(C2H3O2)2(aq) =>
2 HC2H3O2(aq) + Ca(OH)2(aq) = 2 H2O(l) + Ca(C2H3O2)2(aq)
Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
K2O + N2 = K3N2 + O2 =>
6 K2O + 4 N2 = 4 K3N2 + 3 O2
H8C6O7 + OH = H5C6O7 + H2O =>
H8C6O7 + 3 OH = H5C6O7 + 3 H2O
Ca(OH)2(aq) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
Pb3O4 = PbO + O2 =>
2 Pb3O4 = 6 PbO + O2
Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
Ca(s) + H2O(l) = Ca(OH)2 + H2(g) =>
Ca(s) + 2 H2O(l) = Ca(OH)2 + H2(g)
HC2H3O2(aq) + Ca(OH)2(aq) = H2O(l) + Ca(C2H3O2)2(aq) =>
2 HC2H3O2(aq) + Ca(OH)2(aq) = 2 H2O(l) + Ca(C2H3O2)2(aq)
N2O5(g) = NO2(g) + O2(g) =>
2 N2O5(g) = 4 NO2(g) + O2(g)
Zn + C2H4O2 = H2 + Zn(O2CCH3)2 =>
Zn + 2 C2H4O2 = H2 + Zn(O2CCH3)2
LiCN + H3PO4 = Li3PO4 + HCN =>
3 LiCN + H3PO4 = Li3PO4 + 3 HCN
HC2H3O2(aq) + Ca(OH)2(aq) = H2O(l) + Ca(C2H3O2)2(aq) =>
2 HC2H3O2(aq) + Ca(OH)2(aq) = 2 H2O(l) + Ca(C2H3O2)2(aq)
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
N2O5(g) = N2O4(g) + O2(g) =>
2 N2O5(g) = 2 N2O4(g) + O2(g)
Ca(s) + H2O(l) = Ca(OH)2(s) + H2(g) =>
Ca(s) + 2 H2O(l) = Ca(OH)2(s) + H2(g)
(NH4)2C2O4 + CaCl2 = NH4Cl + CaC2O4 =>
(NH4)2C2O4 + CaCl2 = 2 NH4Cl + CaC2O4
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
Ca(s) + H2O(l) = Ca(OH)2(s) + H2(g) =>
Ca(s) + 2 H2O(l) = Ca(OH)2(s) + H2(g)
NaClO2 + NH4Cl = H2O + NH2Cl + NaCl =>
NaClO2 + 2 NH4Cl = 2 H2O + 2 NH2Cl + NaCl
Ca(OH)2(aq) + HNO3(aq) = Ca(NO3)2(aq) + H2O(l) =>
Ca(OH)2(aq) + 2 HNO3(aq) = Ca(NO3)2(aq) + 2 H2O(l)
HC2H3O2(aq) + Ca(OH)2(aq) = H2O(l) + Ca(C2H3O2)2(aq) =>
2 HC2H3O2(aq) + Ca(OH)2(aq) = 2 H2O(l) + Ca(C2H3O2)2(aq)
Zn(OH)2 + H3PO4 = Zn3(PO4)2 + H2O =>
3 Zn(OH)2 + 2 H3PO4 = Zn3(PO4)2 + 6 H2O
HClONaOH = ClONaOH2 =>
HClONaOH = ClONaOH2
Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)
HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + H2O(l) =>
2 HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 H2O(l)
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + HNO3(aq) =>
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + 2 HNO3(aq)
(NH4)2SO4 + NaOH = Na2SO4 + NH3*H2O =>
(NH4)2SO4 + 2 NaOH = Na2SO4 + 2 NH3*H2O
CrCl3 + HBr = CrBr3 + HCl =>
CrCl3 + 3 HBr = CrBr3 + 3 HCl
HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + H2O(l) =>
2 HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 H2O(l)
C6H5ONa + HCl = C6H5OH + NaCl =>
C6H5ONa + HCl = C6H5OH + NaCl
HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + H2O(l) =>
2 HNO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 H2O(l)
(NH4)2C2O4 + CaCl2 = NH4Cl + CaC2O4 =>
(NH4)2C2O4 + CaCl2 = 2 NH4Cl + CaC2O4
Pb(NO3)2 + NAl = Pb(NO3)2NAl =>
Pb(NO3)2 + NAl = Pb(NO3)2NAl
Balance the equation of any chemical reaction
Equations balanced on the previous day |
Equations balanced on 01/04/25
Equations balanced on 02/03/24
Please let us know how we can improve this web app.